Preliminary test results of LGADs from Teledyne e2v for the LHC's High-Luminosity upgrade. (1st October 2022) - Mulvey, J.; Allport, P.; Bell, R.; Bortoletto, D.; Gazi, M.; Gonella, L.; Jordan, D.; Kopsalis, I.; McMahon, S.; Plackett, R.; Stefanov, K.; Villani, E.G.; et al.
Abstract: This paper presents initial testing of the first batch of LGAD sensors fabricated by Teledyne e2v in collaboration with the University of Birmingham, University of Oxford, Rutherford Appleton Laboratory and the Open University. Wafers with different energy and dose of the gain layer implant have been characterised with IV, CV and gain measurements. The same set of measurements were made using PiN diodes fabricated on the same wafer as a reference. Results are in-line with expectations and with LGADs produced at more established vendors. Preliminary results suggests Te2v LGADs have a moderate gain in the order of 10 to 50 before irradiation at operational voltages well below breakdown, as required for optimal timing resolution.